Interpersonal Trust and Friendship Intimacy in Students of The Faculty of Public Health Nusa Cendana University - Hawai, Ragelia Threscia; Keraf, M. K. P. Abdi; Damayanti, Yeni; Junias, Marylin Susanti (Journal of Health and Behavioral Science, 2025)
Interpersonal trust and friendship intimacy are two important aspects of building social relationships, especially in an academic setting. This study aims to determine the relationship between interpersonal trust and friendship intimacy in students of the Faculty of Public Health, Nusa Cendana University. Data were collected through the distribution of interpersonal trust scale and friendship intimacy scale to 322 students. Purposive sampling was used in this study. Data analysis was performed using the Spearman Rank correlation test. The results showed that interpersonal trust in students was in the moderate category (63.0%), while friendship intimacy was also in the moderate category (61.8%). The correlation test results show a coefficient value of 0.508** with a significance level of 0.000 (p < 0.05) which indicates that there is a positive and significant relationship between interpersonal trust and friendship intimacy in students of the Faculty of Public Health, Nusa Cendana University.